LOCAL GOVERNMENT TAX COMPETITION IN CZECHOSLOVAKIA 1918-1938 - J. Haas; L Sedmihradská; J. Ditrich (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The study evaluates tax competition among local governments in Czechoslovakia during the interwar period. Using correlation and regression analysis it proves that (1) local politicians took into account the tax policies of neighbouring jurisdictions when imposing additional tax rates on top of the direct central taxes, (2) there were some regional differences, (3) migration played its role in tax rate setting and (4) the "race-to-the-bottom" did not take place.